The Unknown Groat of Sigismund Augustus - Žukauskas, Donatas (Archaeologia Lituana, 2004)
In this article, the groat of Sigismund Augustus, dated 1549, is introduced. The groat was found in Šiauliai district in 2001. So far it is not clear to whether the mint mark year is false or it is an engraver’s error. Due to the lack of historic references and numismatic material, the little known coin affords us an opportunity to discuss the issues related to its dating. In addition, metrological data point to the fact that the coin hasn’t been forged. The groat of Sigismund Augustus, dated 1549, weight – 2.535 g, diameter – 25 mm, standard – 375. The obverse of the coin bears the head of Sigismundus Augustus and the legend SIGIS AVG REX POL MAG DVX LIT inscribed in between the two rings edging the coin. On the reverse side of the coin the “Vytis” (the mounted knight, the “Vytis”, the historical symbol of the Lithuanian state) with the mintage year below and the heraldic symbol of the House of Gediminas underneath is presented. The legend MONETA MAGNI DVCAT LITVA is inscribed in between the two rings edging the coin. Consequently it should be noted, that the coin resembles the groat of 1546 not just in terms of stylistics. Nevertheless, the mintage date 1546 might be argued because the error of upside down 6 “9” is not characteristic of engravers.Nothing else is left, but awaiting for new foundings and an updated information enabling to solve the problem related to the dating of the considered coin. Anyway, the founding is a contribution to the Grand Dutchy of Lithuania coinage history.